2022
DOI: 10.1136/jitc-2022-005049
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical characterization and clinical translation of pharmacodynamic markers for MK-5890: a human CD27 activating antibody for cancer immunotherapy

Abstract: BackgroundImmune checkpoint inhibitors (ICI) have radically changed cancer therapy, but most patients with cancer are unresponsive or relapse after treatment. MK-5890 is a CD27 agonist antibody intended to complement ICI therapy. CD27 is a member of the tumor necrosis factor receptor superfamily that plays a critical role in promoting responses of T cells, B cells and NK cells.MethodsAnti-CD27 antibodies were generated and selected for agonist activity using NF-кB luciferase reporter assays. Antibodies were hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…The overarching aim of the current study was to develop a potent CD27 agonist suitable for in vivo application. Current efforts to develop agonist antibodies targeting CD27 as well as other members of TNFRSF have been fraught with difficulties due to the vastly different immunostimulatory activities displayed by agents targeting the same receptor ( 21 , 22 , 40 ). Agonism is known to correlate with the ability of antibodies to induce receptor clustering, an attribute that is affected by epitope, antibody hinge flexibility, interaction with FcγRs, and affinity ( 18 , 21 , 36 , 40 42 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overarching aim of the current study was to develop a potent CD27 agonist suitable for in vivo application. Current efforts to develop agonist antibodies targeting CD27 as well as other members of TNFRSF have been fraught with difficulties due to the vastly different immunostimulatory activities displayed by agents targeting the same receptor ( 21 , 22 , 40 ). Agonism is known to correlate with the ability of antibodies to induce receptor clustering, an attribute that is affected by epitope, antibody hinge flexibility, interaction with FcγRs, and affinity ( 18 , 21 , 36 , 40 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no consensus on which of these agents represent the therapeutic of choice for delivering optimal CD27 costimulation. A wide range of agonistic activity has been reported for different anti-CD27 mAbs ( 21 , 22 ). Furthermore, the activity of anti-CD27 mAbs may depend on antibody isotype which affects binding to the inhibitory and activatory Fcγ receptors (FcγRs) ( 18 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another CD27 targeting agonistic mAb in development is MK-5890, which is a humanized IgG1 antibody that is being tested in the clinic as a single agent or in combination with PD-1 blocking agents in advanced solid tumors. The pre-clinical characterization of the mAb demonstrated that it could induce anti-tumor responses as a monotherapy or in combination with PD-1 blockade ( 120 ). Early results suggest an acceptable safety profile, although 24% of patients in the monotherapy group developed grade 3 or 4 adverse events related to treatment.…”
Section: Targeting Cd27mentioning
confidence: 99%
“…Early signs of efficacy with MK-5890 monotherapy or combination, stimulating anti-tumor responses in patients, were observed ( 121 ). Although the mAb could induce transient upregulation of chemokine levels in patients, it also induced decreases in the level of circulating T cells ( 120 ) suggesting that identifying the right dosing regimen will be important for the successful application of this mAb. A recent study in a pre-clinical setting addressed the determinants of agonism for anti-CD27 mAb ( 112 ).…”
Section: Targeting Cd27mentioning
confidence: 99%
“…Similarly, injecting recombinant ES cells successly carrying human CD27 led to the generation of chimeric mice. Then, utilizing Flp‐mediated recombination, the mice carrying the neomycin (NEO) sequence were bred with OZFlp deleter mice to eliminate NEO (Guelen et al, 2022). This method offered the benefit of precision foreign gene injection into ES cells, which is suitable for many complex genes.…”
Section: Strategies For Generating Humanized Micementioning
confidence: 99%